The Influence of Perceived Quality and Perceived Value on E-Wom and Purchase Intention - Rista, Rista; Edastama, Primasatria (International Journal of Economics, Management and Accounting (IJEMA), 2025)
The rapid growth of the highly competitive information technology industry encourages companies to develop effective marketing strategies to improve their competitiveness. This study aims to analyze the influence of perceived quality, social value, personal value, functional value, and e-WOM on laptop purchase intention. This study was conducted using quantitative methods and a descriptive causality approach. The research sample was taken from consumers interested in purchasing a laptop, using a purposive sampling technique. Data were collected through questionnaires completed by 335 respondents in the DKI Jakarta area. Data analysis was conducted using the Structural Equation Modeling Partial Least Square (SEM-PLS) method. The results show that perceived quality, social value, personal value, functional value, and e-WOM have a positive influence on laptop purchase intention. These findings provide an important contribution to understanding the factors that influence consumer decisions in purchasing laptop products. The implications of this study can help companies in designing more effective marketing strategies to increase consumer purchase intention towards their laptop products. This study identified several limitations that need to be addressed to increase the validity and relevance of the results. These limitations include the study's limited sample size within the DKI Jakarta region, its relatively small sample size, and its lack of specific focus on laptop brands or products. Future research is recommended to expand the sample size, increase the sample size, and focus on specific brands to gain a deeper understanding of consumer behavior related to these products.